A look from the Student Scientific Society: Proposal for an Environmental Education program - Despaigne Revé, Anny Fredy; Pérez, Luis Alfonso; Ferreiro Vázquez , Iliana (Revista Minerva, 2022)
The interest in promoting not only knowledge but also skills and values in relation to environmental education of students, given the need and conditions of the current world is the idea that promotes the development of the work that is presented. Starting from the research methods, it is possible to carry out in principle a series of theoretical investigations, which then allow the elaboration of a program of scientific society that responds to the previous demands and also contextualizes the student with his own problems, an element that turns out to be part of the practical contribution of the investigation. It consists of a summary, introduction, development, validation, conclusions, recommendations, annexes and the bibliography.